PENCEGAHAN STUNTING MELALUI PENINGKATAN PENGETAHUAN DAN KESADARAN MASYARAKAT - Puspitasari, Candra Eka; Annisa, Janatul; Putri, Nur Romdani; Azrin, Muhammad; Risckye, Wahyu Maulana; Putri, Ermita (Universitas Mataram, 2025)
Stunting is a health problem caused by chronic or recurrent malnutrition during pregnancy and childhood. The prevalence of stunting in West Nusa Tenggara is higher than the national average, which was 80.8% in 2018. In 2023, there were 497 cases of stunting in Aik Darek village, Batukliang, Central Lombok. To overcome this problem, a stunting prevention socialization activity was held on 10 January 2025 in Aik Darek village, Batukliang, Central Lombok. This activity was attended by 18 participants, consisting of PKK women, pregnant women, and 7 posyandu cadres. The method used was lectures and interactive discussions on the importance of nutrition in pregnancy, exclusive breastfeeding, and consumption of blood supplement tablets. The evaluation of the activity showed that the participants' understanding became better after the discussion process, marked by the participants being able to answer the questions asked by the resource person correctly. This activity is expected to support the government's efforts to reduce stunting rates and improve the quality of Indonesia's future generations